Accounting for the low survival of the Critically Endangered northern bald ibis Geronticus eremita on a major migratory flyway. Issue 2 (13th February 2014) - Serra, G.; Lindsell, J. A.; Peske, L.; Fritz, J.; Bowden, C. G. R.; Bruschini, C.; Welch, G.; Tavares, J.; Wondafrash, M.
Abstract: The poor survival rate of immature northern bald ibises Geronticus eremita during their first years spent outside the natal site is driving the last known wild colony of the migratory eastern population to extinction. To inform emergency conservation action for this Critically Endangered species we investigated the distribution range and behaviour of immature birds in passage and wintering areas, and the threats to which they are subject. We integrated recent satellite telemetry data with visual observations spanning 130 years. We assessed threats across the range, using satellite tracking and field surveys. Our results show that during the years before they return to the natal site in Syria, immature northern bald ibises reside away from the recently identified adult wintering site in the central Ethiopian highlands. They occur mainly across the northernmost 70–80% of the adult migratory range. Historical records suggest that immature birds spend more time along the western Arabian Peninsula now than in the past. This range shift exposes them for longer periods to threats, such as hunting and electrocution on power lines, which are absent from the wintering site used by adult birds. We suggest that other threatened and declining bird species sharing the same flyway probably face the same threats during migration.